On Display - Caylor, Jeff (Raton, NM Raton Range, 1979)
Article is about a donation of Uncle Dick Wootten's stove donated by John Southwell
Newspaper article + Photograph of Erma Carlini
Master list item #: 88
File location is in the Raton file Cabinet
Keywords: Carlini, Erma -- Volunteer VFW auxiliry Worker; Wootten, Dick; Southwell, John; Exhibit Donations; New Exhibits; Museum Exhibits; Raton, New Mexico